The influence of key process parameters on melt pool geometry in direct energy deposition additive manufacturing systems. (February 2021) - Sampson, Robert; Lancaster, Robert; Sutcliffe, Mark; Carswell, David; Hauser, Carl; Barras, Josh
Highlights: Directional emittance algorithm successfully used to perform a detailed parametric study. Increasing powder mass flow rate widens the resultant melt pool. When using high laser power settings, a larger body of molten material is formed. Increasing PMFR at low laser power settings does not influence melt pool width. Increasing path velocity reduces melt pool width for all laser power settings. Abstract: The measurement of melt pool width has proven to be critical in the development of advanced control systems, defect detection algorithms and understanding the influence of parameter changes on build quality in additive manufacturing processes. Parametric studies are performed on new materials and builds to help identify optimal parameter settings for final components. Many parametric iterations are often required to produce optimal components, which requires in-depth process/material knowledge from highly skilled engineers. Having fundamental knowledge of parametric interaction and melt pool mechanics is key in developing state of the art additive manufacturing components. This paper addresses the need for complex parametric interaction understanding in additive manufacturing processes by providing a detailed parametric study using directional emittance melt pool edge detection techniques.